2022
DOI: 10.1097/fjc.0000000000001185
|View full text |Cite
|
Sign up to set email alerts
|

Nanobodies as Probes and Modulators of Cardiovascular G Protein–Coupled Receptors

Abstract: Understanding the activation of G protein-coupled receptors (GPCRs) is of paramount importance to the field of cardiovascular medicine due to the critical physiological roles of these receptors and their prominence as drug targets. Although many cardiovascular GPCRs have been extensively studied as model receptors for decades, new complexities in their regulation continue to emerge. As a result, there is an ongoing need to develop novel approaches to monitor and to modulate GPCR activation. In less than a deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 133 publications
0
7
0
Order By: Relevance
“…Another very important target for cardiovascular medicine is the G-protein coupled receptors (GPCRs) and various nanobody-based strategies have been employed in order to study their structure, pharmacokinetics, and expression modulation [ 58 ]. By using a library of synthetic camelid antibody fragments, a series of nanobodies that can interact with angiotensin II type 1 receptor (AT1R) were discovered.…”
Section: Nanobodies For Cardiovascular Disease Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Another very important target for cardiovascular medicine is the G-protein coupled receptors (GPCRs) and various nanobody-based strategies have been employed in order to study their structure, pharmacokinetics, and expression modulation [ 58 ]. By using a library of synthetic camelid antibody fragments, a series of nanobodies that can interact with angiotensin II type 1 receptor (AT1R) were discovered.…”
Section: Nanobodies For Cardiovascular Disease Therapymentioning
confidence: 99%
“…Further studies showed that, for instance, clone NbAT110 helped determine the structural characteristics of the AT1R receptor and revealed how peptides bind and activate it, which until now, because of the size and flexibility of the peptides that bind to this receptor, was not very clear. Furthermore, some new information regarding receptor-peptide binding was revealed, such as a partial β-barrel at the N-terminal end of the receptor, a β-hairpin, and the N-terminus of the binding peptide [ 58 ].…”
Section: Nanobodies For Cardiovascular Disease Therapymentioning
confidence: 99%
“…Along with highly specialized components of GPCR signaling, endogenous allosteric regulators of GPCR include some classes of antibodies produced against extracellular regions of receptors, small proteins, oligopeptides, steroids, fatty acids, amino acids, and even simple ions [91,[94][95][96][97][98][99][100]. Some allosteric regulators specifically affect a particular receptor or closely related GPCRs, while others are non-specific and affect the activity of a large number of GPCRs belonging to different families.…”
Section: Diversity Of Endogenous Allosteric Regulators Of Gpcrsmentioning
confidence: 99%
“…These include resolving the crystal structures of β 2 AR in complex with agonist/Gs [6][7][8]. As highlighted in various reviews [9][10][11][12][13], this methodology has also proved effective in resolving the active-state crystal structures of other GPCRs for imaging and modulating GPCR function and as a new class of potential GPCR-targeted therapeutics.…”
Section: Introductionmentioning
confidence: 99%